O11.6 Trends in chlamydia screening and pap testing among US females by age and race, national survey of family growth, 2006–2017. (14th July 2019) - Haderxhanaj, Laura; Dieselz, Jill; Peterman, Thomas
Abstract : Background: From 2010 to 2017, rates of chlamydia declined among young black women in the United States but increased among all white women. Around the same time, the recommended age for cervical cancer screening was raised to > 21 years. Changes in reported chlamydia may be due to changes in screening. We examined trends in chlamydia screening and Pap screening among women by age and race. Methods: Data are from the four most recent waves of the National Survey of Family Growth (2006–2010, 2011–2013, 2013–2015, 2015–2017). To assess trends in chlamydia screening and Pap tests, we used chi-square and logistic regression analysis to examine self-reported screening in the past 12 months among sexually active women (oral, vaginal, and/or anal sex with a male partner in the past 12 months) by age (15–24, 25–44 years), race (non-Hispanic black, white), and lifetime number of male sex partners (1, 2–4, 5+). Results: There were 23, 171 sexually active women. Self-reports of Pap testing in the past 12 months decreased for young women (black: 72.5–53.6%, p<0.01; white: 67.9–42.2%, p<0.0001) and older white women (71.5–61.9%, p<0.001) from 2006–2010 to 2015–2017. Self-reports of chlamydia screening did not significantly decrease for younger women (black: 57.6–54.2%, p=0.9040; white: 37.4–34.4%, p=0.1716) and increased for older women (black: 37.6–50.6%, p<0.01; white: 15.4–24.3%, p<0.0001). Overall, women who were younger (RR=2.3, 95%CI: 2.1, 2.5), non-Hispanic black (RR=2.0, 95%CI: 1.9, 2.2), had more than one lifetime male sex partner (2–4: RR=1.7, 95%CI: 1.4, 2.0; 5+: AOR=3.0, 95%CI: 2.5, 3.6), and received a Pap test in the past 12 months (RR=3.4, 95%CI: 3.0, 3.8) were more likely to be screened for chlamydia in the past 12 months. Conclusion: Self-reports of cervical cancer screening decreased but self-reports of chlamydia screening remained stable in young women and increased in women > 25 years. Chlamydia screening remains below national recommendations, especially for young women. Disclosure: No significant relationships.